Analisis Strategi Produksi dan Pemasaran pada UMKM Bakso 43 Kelurahan Jatiwangi - Ita Purnama; Aida Zulwahidah; Dwi Rahmadani Kadiri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
UMKM Bakso 43 located in Jatiwangi Village is one of the micro businesses in the culinary field that sells meatball products at home. This business experiences obstacles in production consistency and limited marketing strategies. This study aims to analyze the production and marketing strategies of UMKM Bakso 43 and provide solutions and directions for future development. The research method used is descriptive qualitative through observation, interviews, and direct assistance. The marketing strategy focused on in this study is through the Facebook social media platform. The results show that production efficiency can be increased through production rescheduling and recording raw materials, while digital marketing through Facebook can significantly increase consumer reach. This study concludes that collaboration between strengthening production management and simple digital marketing can be the main driver of UMKM development